Financial literacy, investment and personal financial management nexus: Empirical evidence on private sector employees - Clement Oppong; Abukari Salifu Atchulo; Ellis Kofi Akwaa-Sekyi; Dianne Dogbey Grant; Silas Apealete Kpegba (Cogent Business & Management, 2023)
This paper aims to examine financial literacy, investment decisions and personal financial management nexus among the Small and Medium Enterprises (SMEs) employees in the private sector in Ghana. The study employed a structured questionnaire with close-ended questions to collect data from 400 respondents using convenience sampling approach. The study adopted a Partial Least Square Structural Equation Model (PLS-SEM) for analysis. The results of the study reveal a positive significant link between personal financial management and financial literacy; a positive significant correlation between investment decision and personal financial management; and a mediated effect of investment decision between financial literacy and personal financial management. This implies that individuals need to receive training in appropriate money management techniques in order to foster a more competitive and effective market for consumption and savings. The theoretical contribution of this study follows the theory of planned behavior phenomenon where the psychology factors influence the investment decisions of individuals. This present study originates by examining financial literacy, personal financial management and investment decision nexus among private sector employees.
Keywords: 650; financial literacy; investment decision; personal financial management